Recreational microplastics as emerging pollutants: effects of crumb rubber leachate across ecosystems - Sharon T. Pochron; Xiayan Ye; Amith S. Maroli; Arjun K. Venkatesan; Samy Sasoun; Thomas J. Gaylor; Mary Girgis; Morgan A. Jacobellis; Alec Miranda; Johanna A. Mitra; Grace Van Gelder; Samantha H. Byrne; et al. (Chemosphere, 2026)

Intraspecific comparative micromorphology of the Heliamphora pulchella (Sarraceniaceae) species complex - Jonathan Charles Martin; Joseph Robb Terhune Walston; Kenneth Michael Cameron (Flora, 2026)

Metabolic stability and effects of microsomal enzymes on the activity of the sonic hedgehog pathway inhibitor piperonyl butoxide - Kenneth S. Rivera-González; Cameron O. Scarlett; Robert J. Lipinski (Toxicology in Vitro, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.

Diagenetic and sequence stratigraphic controls on reservoir quality in the Upper Jurassic Smackover Formation, southern Arkansas, USA - Cameron J. Manche; Jim Markello; Juan Carlos Laya; Mike Pope; Kenneth Fritsche; Kevin Hill (Marine and Petroleum Geology, 2025)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Time Delta Head Impact Frequency: An Analysis on Head Impact Exposure in the Lead Up to a Concussion: Findings from the NCAA-DOD Care Consortium - Jack Seifert; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Larry Riggen; Stefan Duma; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Joshua Goldman; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2022)
Sport-related concussions can result from a single high magnitude impact that generates concussive symptoms, repeated subconcussive head impacts aggregating to generate concussive symptoms, or a combined effect from the two mechanisms. The array of symptoms produced by these mechanisms may be clinically interpreted as a sport-related concussion. It was hypothesized that head impact exposure resulting in concussion is influenced by severity, total number, and frequency of subconcussive head impacts. The influence of total number and magnitude of impacts was previously explored, but frequency was investigated to a lesser degree. In this analysis, head impact frequency was investigated over a new metric called ‘time delta’, the time difference from the first recorded head impact of the day until the concussive impact. Four exposure metrics were analyzed over the time delta to determine whether frequency of head impact exposure was greater for athletes on their concussion date relative to other dates of contact participation. Those metrics included head impact frequency, head impact accrual rate, risk weighted exposure (RWE), and RWE accrual rate. Athletes experienced an elevated median number of impacts, RWE, and RWE accrual rate over the time delta on their concussion date compared to non-injury sessions. This finding suggests elevated frequency of head impact exposure on the concussion date compared to other dates that may precipitate the onset of concussion.

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

Using Multiple Ecological Models to Inform Environmental Decision-Making - Kristy A. Lewis; Kenneth A. Rose; Kim de Mutsert; Shaye Sable; Cameron Ainsworth; Damian C. Brady; Howard Townsend (Frontiers in Marine Science, 2021)
Coastal ecosystems are experiencing degradation from compound impacts of climate change and multiple anthropogenic disturbances. These pressures often act synergistically and complicate designing effective conservation measures; consequently, large-scale coastal restoration actions become a wicked problem. The purpose of this study was to use two different food web models in a coordinated manner to inform resource managers in their assessment of the ecological effects of a large-scale marsh restoration project. A team was formed that included the model developers and outside scientists, who were asked to use available model results of the calibrated simulations of an Ecopath with Ecosim (EwE) model and a Comprehensive Aquatic Systems Model (CASM), both designed to describe the structure and energetics of the Barataria Bay, Louisiana, United States food web. Both models offer somewhat different depictions of the predator-prey and competitive interactions of species within the food web, and how environmental conditions affect the species biomass pools and energetics. Collectively, the team evaluated the strengths of each model and derived a common set of indicator variables from model outputs that provided information on the structure and energy flow of the simulated food web. Considering the different modeling structures and calibration approaches, indicators were interpreted within and between models. Use of both models enabled a robust determination that: (1) Detritus plays a vital role in the energetics of the system; (2) The food web responds to spring high flow seasons by increasing productivity through specific, dominant pathways; (3) The trophic pyramid is truncated; (4) Compared to other estuaries, this system has redundant pathways for energy transfer. These findings indicate that the food web appears to be resilient to disturbance because of a detritus energy reserve, most consumer biomass consists of low trophic level, high turnover species, and redundant energy pathways exist. This information provides context to decision-makers for assessing possible basin-scale impacts on fish and shellfish resources of a proposed large-scale restoration project. The use of multiple models in a coordinated but not overly constrained way, as demonstrated here, provides a significant step toward co-production of knowledge for use in resource management decisions.

Effects of Petroleum By-Products and Dispersants on Ecosystems - Kenneth Halanych; Cameron Ainsworth; Erik Cordes; Richard Dodge; Markus Huettel; Irving Mendelssohn; Steven Murawski; Claire Paris-Limouzy; Patrick Schwing; Richard Shaw; Tracey Sutton (Oceanography, 2021)
Gulf of Mexico (GOM) ecosystems are interconnected by numerous physical and biological processes. After the Deepwater Horizon (DWH) disaster, these ecological processes facilitated dispersal of oil-spill toxicants or were damaged and broken. A considerable portion of post-DWH research focused on higher levels of biological organization (i.e., populations, communities, and ecosystems) spanning at least four environments (onshore, coastal, open ocean, and deep benthos). Damage wrought by the oil spill and mitigation efforts varied considerably across ecosystems. Whereas all systems show prolonged impacts because of cascading effects that impacted functional connections within and between communities, deep-sea and mesopelagic environments were particularly hard hit and have shown less resilience than shallow environments. In some environments, such as marshes or the deep-sea benthos, products from the spill are still biologically accessible. Some shallow ecosystems show signs of recovery, and populations of some species show resilience; however, a return to a “pre-spill” state is questionable. Importantly, habitats in which large amounts of energy flow through the ecosystem (marshes, coastal regions) recovered more quickly than low energy habitats (deep-sea benthos). Functional interactions between Gulf of Mexico systems are more complex and widespread than generally recognized. Moreover, ecosystems in the Gulf are subject to multiple stressors that can combine to impart greater, and less predictable, impacts. To help mitigate the effects of future insults, we identified four salient areas of research that should be addressed for each of the major environments within the GOM: establishing monitoring systems; quantifying coupling between GOM ecosystems; developing criteria for assessing the “vulnerability” and “resilience” of species, communities, and ecosystems; and developing holistic predictive modeling.

Concussion Risk Between Individual Football Players: Survival Analysis of Recurrent Events and Non-events - Steven Rowson; Eamon T. Campolettano; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry Riggen; Jason P. Mihalik; Alison Brooks; Kenneth L. Cameron; Steven J. Svoboda; Megan N. Houston; et al. (Annals of Biomedical Engineering, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

PTIS Potato Herbarium Transferred to WIS, the Wisconsin State Herbarium - David M. Spooner; Philipp Simon; John B. Bamberg; Kenneth M. Cameron (American Journal of Potato Research, 2019)

Repetitive Head Impact Exposure in College Football Following an NCAA Rule Change to Eliminate Two-A-Day Preseason Practices: A Study from the NCAA-DoD CARE Consortium - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Stefan Duma; Jason P. Mihalik; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Megan N. Houston; Jonathan Jackson; et al. (Annals of Biomedical Engineering, 2019)

Accounting for Variance in Concussion Tolerance Between Individuals: Comparing Head Accelerations Between Concussed and Physically Matched Control Subjects - Steven Rowson; Eamon T. Campolettano; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry Riggen; Jason P. Mihalik; Kevin M. Guskiewicz; Christopher Giza; Alison Brooks; Kenneth Cameron; et al. (Annals of Biomedical Engineering, 2019)

Factors Affecting Head Impact Exposure in College Football Practices: A Multi-Institutional Study - Eamon T. Campolettano; Steven Rowson; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry D. Riggen; Jason Mihalik; Alison Brooks; Kenneth Cameron; Christoper C. Giza; Thomas McAllister; et al. (Annals of Biomedical Engineering, 2019)

Level of Agreement Between Human-Rated and Instrumented Balance Error Scoring System Scores - Megan N. Houston; Matthew C. Hoch; Steven R. Malvasi; Karen Y. Peck; Steven J. Svoboda; Kenneth L. Cameron (Annals of Biomedical Engineering, 2019)

Comparison of Head Impact Exposure Between Concussed Football Athletes and Matched Controls: Evidence for a Possible Second Mechanism of Sport-Related Concussion - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Stefan M. Duma; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Darren Campbell; John P. DiFiori; Christopher C. Giza; et al. (Annals of Biomedical Engineering, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

High-depth whole genome sequencing of an Ashkenazi Jewish reference panel: enhancing sensitivity, accuracy, and imputation - Todd Lencz; Jin Yu; Cameron Palmer; Shai Carmi; Danny Ben-Avraham; Nir Barzilai; Susan Bressman; Ariel Darvasi; Judy H. Cho; Lorraine N. Clark; Zeynep H. Gümüş; Vijai Joseph; et al. (Human Genetics, 2018)

Spiranthes igniorchis (Orchidaceae), a new and rare cryptic species from the south-central Florida subtropical grasslands - Matthew C. Pace; Steve L. Orzell; Edwin L. Bridges; Kenneth M. Cameron (Brittonia, 2017)

Biogeography of the cosmopolitan sedges (Cyperaceae) and the area‐richness correlation in plants - Daniel Spalink; Bryan T. Drew; Matthew C. Pace; John G. Zaborsky; Julian R. Starr; Kenneth M. Cameron; Thomas J. Givnish; Kenneth J. Sytsma (Journal of Biogeography, 2016)
Aim Across angiosperm families, the area occupied by a family is strongly correlated with its richness. We explore the causes of this area‐richness correlation using the cosmopolitan family, Cyperaceae Juss., as a model. We test the hypothesis that, despite a proposed tropical origin, temperate lineages in the family diversified at elevated rates. We test the hypothesis that the area‐richness correlation is maintained within intrafamilial clades, and that this relationship could be described as a function of niche space. We also test the hypothesis that the partitioning of geographical and ecological space, not the extent of this space, is the factor most closely associated with clade richness. Location Cosmopolitan. Methods We use molecular data from four genes sequenced in 384 taxa to develop a chronogram of Cyperaceae. We then develop a model of ancestral ranges and measure rates of diversification throughout the history of the family. Integrating data from over 4,800,000 digitized herbarium records, we characterize the range and niche of more than 4500 species and test for correlations of the species richness maintained within clades with range size, range partitioning, range overlap, niche, clade age and rate of diversification. Results Cyperaceae originated in South America in the late Cretaceous and subsequently dispersed throughout the globe. Of three increases in diversification rate, two occurred in the temperate Northern Hemisphere. The variable most closely associated with clade richness is the partitioning of geographical space by species within each clade. Main conclusions We show that species‐rich clades in Cyperaceae are not only more widespread, occupy more niche space, and diversify more quickly, but also exhibit patterns that are consistent with the partitioning of geographical and ecological space as a major correlate to diversification.

Discordance between morphological and taxonomic diversity: land snails of oceanic archipelagos - Kostas A. Triantis; François Rigal; Christine E. Parent; Robert A. D. Cameron; Bernd Lenzner; Aristeidis Parmakelis; Norine W. Yeung; María R. Alonso; Miguel Ibáñez; António M. de Frias Martins; Dinarte N. F. Teixeira; Owen L. Griffiths; et al. (Journal of Biogeography, 2016)
Aim Morphological and taxonomic diversity are intuitive measures of biological diversity. Previous studies have shown discordance between these measures at large spatial and temporal scales, but the implications of this pattern for the underlying processes are not understood. Using oceanic archipelagos as spatial units, we examine potential links between the morphological and taxonomic diversity of their land snail faunas in a biogeographical framework. Location Eleven major oceanic archipelagos. Methods For each archipelago, we assembled lists of indigenous land snail species, classified by family and genus, with shell height and width for each species (1723 species in total). We used biogeographic and climatic variables as potential predictors of diversity patterns. We employed regression analyses to evaluate (1) whether morphological diversity scales with taxonomic diversity at the species, genus or family level, and (2) whether morphological and taxonomic diversity correlate similarly with biogeographic/climatic factors. We also assessed which taxonomic level contributes most to morphological variation within archipelagos. Results Morphological diversity across archipelagos was strongly related to genus but not species richness. Within archipelagos, morphological variation reflected differences among genera and families but not species. Species richness was best explained by archipelago area, but morphological diversity was not significantly related to any of the physical features of archipelagos. Main conclusions Across archipelagos, species richness and morphological diversity of land snail faunas are decoupled. The relationship between species richness and the available ecological space (captured mainly by area) indicates the prevalence of niche‐based processes while, for morphological diversity, the strong conservatism of morphology at the genus level suggests the presence of diversification‐based limits. Assuming genera effectively reflect diversification, our findings indicate that morphological space on oceanic archipelagos depends primarily on the number of evolutionary units that have colonized and/or diversified through time.

Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal - Thomas J. Givnish; Daniel Spalink; Mercedes Ames; Stephanie P. Lyon; Steven J. Hunter; Alejandro Zuluaga; Alfonso Doucette; Giovanny Giraldo Caro; James McDaniel; Mark A. Clements; Mary T. K. Arroyo; Lorena Endara; et al. (Journal of Biogeography, 2016)
Aim Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal ( LDD ) in generating orchid diversity. Location Global. Methods Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma ( HPD : 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.

Bacteria influence mountain pine beetle brood development through interactions with symbiotic and antagonistic fungi: implications for climate-driven host range expansion - Janet Therrien; Charles J. Mason; Jonathan A. Cale; Aaron Adams; Brian H. Aukema; Cameron R. Currie; Kenneth F. Raffa; Nadir Erbilgin (Oecologia, 2015)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

On the Value of Taxonomy, Phylogeny, and Systematics to Orchid Conservation: Implications for China’s Yachang Orchid Reserve - Kenneth M. Cameron (The Botanical Review, 2010)

Molecular evidence on the species status and phylogenetic relationships of Spiranthes parksii, an endangered orchid from Texas - Lucy A. Dueck; Kenneth M. Cameron (Conservation Genetics, 2008)

book review - Kenneth M. Cameron (Brittonia, 2008)

Suggested Guidelines for Use of Avian Species as Biomonitors - Simon Hollamby; Josephine Afema-Azikuru; Samuel Waigo; Kenneth Cameron; A. Rae Gandolf; Amanda Norris; James G. Sikarskie (Environmental Monitoring and Assessment, 2006)

Phylogenetic relationships in Peniocereus (Cactaceae) inferred from plastid DNA sequence data - Salvador Arias; Teresa Terrazas; Hilda J. Arreola-Nava; Monserrat Vázquez-Sánchez; Kenneth M. Cameron (Journal of Plant Research, 2005)

Recircumscription of the monocotyledonous family Petrosaviaceae to include Japonolirion - Kenneth M. Cameron; Mark W. Chase; Paula J. Rudall (Brittonia, 2003)

Book reviews - C. Moran; Wayt Thomas; Marccus Alves; William R. Buck; Kenneth M. Cameron (Brittonia, 2001)

Icones Pleurothallidinarum XV–XIX. By Carlyle Luer - Kenneth M. Cameron (Brittonia, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)